Neurobiological roots of language in primate audition: common computational properties. Issue 3 (March 2015) - Bornkessel-Schlesewsky, Ina; Schlesewsky, Matthias; Small, Steven L.; Rauschecker, Josef P.
Highlights We present a unified dual-streams model for primate audition and human language. Dorsal/ventral stream computations in language are grounded in primate audition. Ventral stream: auditory object recognition and commutative combinatorics. Dorsal stream: hierarchical predictive coding of sequences from phonemes to discourse.